A study on parametric approaches to compare areas under two correlated ROC curves - Sumi, Nahid Sultana; Hossain, Md Akhtar (Bangladesh Journal of Scientific Research, 2012)
No abstract available DOI: http://dx.doi.org/10.3329/bjsr.v25i1.13051 Bangladesh J. Sci. Res. 25(1): 61-71, 2012